DOI: 10.14264/uql.2015.1017
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanism of drug delivery from thickened fluids to aid swallowing of medications

Abstract: Medications are often crushed and mixed with foods or fluids to aid drug delivery for those who cannot or prefer not to swallow whole tablets or capsules. Dysphagic patients have the added problem of being unable to safely swallow fluids, so thickeners are added to ensure safe swallowing. These thickened fluids are then also used to deliver crushed medications in replacement of water. This thesis explores the influence of thickened water co-administration on drug release in gastric fluid, the effect of rheolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 147 publications
(207 reference statements)
0
1
0
Order By: Relevance
“…The in vivo absorption of crushed paracetamol tablets mixed with xanthan gum-based dysphagia-oriented thickeners was substantially faster than what was predicted from in vitro dissolution tests [21]. It has been suggested that this is associated with changes that occur to the bolus structure during deglutition that change the form of the bolus by the time it reaches the stomach, which, in turn, might increase drug release [11,22].…”
Section: Introductionmentioning
confidence: 96%
“…The in vivo absorption of crushed paracetamol tablets mixed with xanthan gum-based dysphagia-oriented thickeners was substantially faster than what was predicted from in vitro dissolution tests [21]. It has been suggested that this is associated with changes that occur to the bolus structure during deglutition that change the form of the bolus by the time it reaches the stomach, which, in turn, might increase drug release [11,22].…”
Section: Introductionmentioning
confidence: 96%